Insights in the biocatalyzed hydrolysis, esterification and transesterification of waste cooking oil with a vegetable lipase - Mateos, Paula Stefania (2020)
The present contribution investigates the biocatalytic performance of the lipase obtained from the latex of the native plant known as Araujia sericifera (ASL) in the hydrolysis followed by the esterification of released free fatty acids and transesterification of glycerides of sunflower waste cooking oil WCO. A specific enzymatic activity of 719.05 μmol mg−1 h−1 (60 % conversion of triglycerides towards free fatty acids) was obtained in the hydrolysis of WCO with 0.05 % of biocatalyst (typically, 10.0 g WCO and 5.0 mg of enzyme) and 50 % w/w of water added in 30 min of reaction at 25 °C in homogeneous type of reaction system. The lipase has the capacity to catalyze the hydrolysis of the triglycerides mainly towards monoglycerides and diglycerides in a lesser extent. The released FFAs and the remaining glycerides reacted in tandem by addition of short chain alcohols immediately after the hydrolysis (without addition of more enzyme to the reaction media). Above 90 % conversion of the FFAs was obtained with methanol, ethanol, n-propanol and n-butanol at contents as low as 1:0.2 oil: alcohol molar ratio at 25 °C. The transesterification of the remaining monoglycerides (about 20 %) was also observed although no further reaction of the triglycerides was detected even under a great excess of alcohol.